Passive targeting of nanoparticles to cancer: A comprehensive review of the literature - BAZAK, REMON (D.A. Spandidos, 2014)
Cancer remains the one of the most common causes of mortality in humans; thus, cancer treatment is currently a major focus of investigation. Researchers worldwide have been searching for the optimal treatment (the ‘magic bullet’) that will selectively target cancer, without afflicting significant morbidity. Recent advances in cancer nanotechnology have raised exciting opportunities for specific drug delivery by an emerging class of nanotherapeutics that may be targeted to neoplastic cells, thereby offering a major advantage over conventional chemotherapeutic agents. There are two ways by which targeting of nanoparticles may be achieved, namely passive and active targeting. The aim of this study was to provide a comprehensive review of the literature focusing on passive targeting.